Prothrombotic State Induced by Middle-Distance Endurance Exercise in Middle-Aged Athletes - Lippi, Giuseppe; Salvagno, Gian Luca; Tarperi, Cantor; Gelati, Matteo; Montagnana, Martina; Danese, Elisa; Festa, Luca; Sanchis-Gomar, Fabian; Favaloro, Emmanuel J.; Schena, Federico (Seminars in Thrombosis and Hemostasis, 2018)
Since the impact of possible prothrombotic factors on blood coagulation resulting from exercise remains elusive, this study investigated the acute effects of middle-distance endurance running on blood coagulation parameters in middle-aged athletes. The study population consisted of 33 male endurance runners who were engaged in a 21.1 km run under competitive conditions. Blood samples were collected before the run, immediately after the run, and 3 hours after run completion. Samples were assessed for activated partial thromboplastin time (APTT), prothrombin time (PT), fibrinogen, D-dimer, factor VIII (FVIII), von Willebrand factor antigen (VWF:Ag), endogenous thrombin potential (area under the curve of thrombin generation [TGA-AUC]), and peak thrombin generation (TGA-PK). Post-run variations were expressed as delta (Δ). At baseline, APTT was found to be significantly associated with ABO blood group, VWF:Ag, and FVIII; fibrinogen with age; VWF:Ag with BMI, training regimen, and ABO blood group; APTT with FVIII; FVIII with VWF:Ag and ABO blood group; APTT with VWF:Ag; and TGA-PK with ABO blood group, PT, and TGA-AUC. Immediately after the run, statistically significant increases were observed for PT, D-dimer, VWF:Ag, and FVIII, while statistically significant reductions could be observed for APTT, TGA-AUC, and TGA-PK. Fibrinogen values remained unchanged. Significant correlations were observed between Δ VWF:Ag and Δ FVIII, Δ APTT and Δ VWF:Ag, Δ APTT and Δ FVIII, Δ TGA-AUC and Δ TGA-PK, and between Δ D-dimer and Δ TGA-AUC and Δ TGA-PK. No Δ variation was associated with running time. The results of this study seemingly suggest that middle-distance competitive running may evoke several prothrombotic changes in blood coagulation.
Keywords: blood coagulation; hemostasis; thrombin generation; physical activity